Treadmill exercise alleviates short-term memory impairment in 6- hydroxydopamine-induced Parkinson’s rats - Cho, Han-Sam; Shin, Mal-Soon; Song, Wook; Jun, Tae-Won; Lim, Baek-Vin; Kim, Young-Pyo; Kim, Chang-Ju (Journal of exercise rehabilitation, 2013)
Progressive loss of dopaminergic neurons in substantia nigra is a key pathogenesis of Parkinson’s disease. In the present study, we investi-gated the effects of treadmill exercise on short-term memory, apoptotic dopaminergic neuronal cell death and fiber loss in the nigrostriatum, and cell proliferation in the hippocampal dentate gyrus of Parkinson’s rats. Parkinson’s rats were made by injection of 6- hydroxydopamine (6-OHDA) into the striatum using stereotaxic instrument. Four weeks after 6-OHDA injection, the rats in the 6- OHDA-injection group exhibited significant rotational asymmetry following apomorphine challenge. The rats in the exercise groups were put on the treadmill to run for 30 min once a day for 14 consecutive days starting 4 weeks after 6-OHDA injection. In the present results, extensive degeneration of the dopaminergic neurons in the substantia nigra with loss of dopaminergic fibers in the striatum were produced in the rats without treadmill running, which resulted in short-term memory impairment. However, the rats performing treadmill run-ning for 2 weeks alleviated nigrostriatal dopaminergic cell loss and alle-viated short-term memory impairment with increasing cell proliferation in the hippocampal dentate gyrus of Parkinson’s rats. The present re-sults show that treadmill exercise may provide therapeutic value for the Parkinson’s disease.